The effect of predation risk on cash holdings: Empirical evidence from the U.S. property‐liability insurance industry. Issue 3 (4th September 2019) - Che, Xin; Fier, Stephen G.; Liebenberg, Andre P.
Abstract: Corporate cash holdings play a significant role in the U.S. property‐liability insurance industry yet the topic of insurer cash holdings policy has largely been overlooked by prior empirical research. While a number of studies have investigated firm‐specific factors related to cash holdings in the insurance industry, prior research has not examined how market concentration and potential predation risk impact cash holdings. We propose a new measure of market concentration and provide evidence in support of the predation risk theory. Specifically, we show that insurers exposed to more concentrated markets tend to hold more cash. Furthermore, the relation between market concentration and cash holdings is influenced by access to internal capital. While unaffiliated insurers without access to internal capital hold greater levels of cash in more concentrated markets, group insurers with access to internal capital do not hold greater levels of cash to mitigate predation risk.